Advancing IoT Platforms Interoperability. - Vermesan, Ovidiu. (River Publishers, 2018)
This white paper provides an insight regarding interoperability in the IoT platforms and ecosystems created and used by IoT-EPI. The scope of this document covers the interoperability aspects, challenges and approaches that cope with interoperability in the current existing IoT platforms.